Melanoma susceptibility variant rs869330 in the MTAP gene is associated with melanoma outcome. Issue 6 (December 2019) - Marasigan, Vivien; Güvenç, Canan; van den Oord, Joost J.; Stas, Marguerite; Boecxstaens, Veerle; Bechter, Oliver; Wolter, Pascal; Lambrechts, Diether; Garmyn, Marjan
Abstract : The rising incidence of cutaneous melanoma (CM), an aggressive skin cancer, emphasizes the need for novel biomarkers to guide personalized care and better predict outcome. Genetic factors including germline risk variants are promising candidates for this aim. We explored the association between germline risk variants and melanoma outcome in a large genetically homogenous Belgian melanoma population, focusing on single nucleotide polymorphisms which generated the highest association with melanoma susceptibility. Between 2004 and 2014, blood samples of 1088 patients with histologically confirmed CM were collected and genotyped for nine variants. Cox proportional hazard models were used to assess the association between each single nucleotide polymorphism and relapse-free survival and overall survival, adjusted by age, sex, melanoma stage, site, and subtype. We identified significant associations for rs869330 (in the methylthioadenosine phosphorylase – MTAP gene) with overall survival (hazard ratio = 0.760, P = 0.048, 95% confidence interval: 0.580–0.998) and relapse-free survival (hazard ratio = 0.800, P = 0.020, 95% confidence interval: 0.650–0.970). This exploratory study is the first to show a significant association between the rs869330 variant (in the MTAP gene) and outcome in a large CM population. Abstract : Supplemental Digital Content is available in the text.